Nichtwissen lenken Nanotechnologie in Europa und den Vereinigten Staaten - Kurath, Monika (Wissenschafts- und Technikforschung, 2017)
This book develops a fresh and challenging perspective on ignorance. Drawing on a wide and diverse range of expert interviews and policy documents from nanotechnology discourses in Britain, Germany, the US and the EU, it argues that contemporary knowledge societies lack robust instruments with which they can regulate technosciences. Due to the high amount of ignorance inherent in technosciences and emerging technologies, a broad range of societal actors are involved in assessing and regulating them. This leads to a situation where expertise is being delegated to society as a whole, the boundaries between reliable and speculative knowledge are merging and responsibilities specific to certain institutions are dissolving.